Two-Stage Conversion of Used Cooking Oil to Biodiesel Using Ion Exchange Resins as Catalysts - Sumaiya, Zainal Abidin; Mohammed, Misbahu Ladan; Saha, Basudeb (MDPI, 2023)
This study focuses on the development of a novel two-stage (esterification–transesterification) synthesis of biodiesel from used cooking oil (UCO) using ion exchange resins as catalysts. Esterification of the UCO has been conducted using various types of ion exchange resin catalysts. Purolite D5081, a hyper cross-linked resin, showed the best catalytic performance among all the catalysts investigated, with 92% of free fatty acid (FFA) conversion. The transesterification of pre-treated used cooking oil (P-UCO) was carried out sequentially using several acidic and basic ion exchange resin catalysts. In the screening process, the Diaion PA306s catalyst showed the best catalytic performance and was selected for the optimisation study. A triglyceride conversion of ca. 75% was recorded at the optimum reaction conditions (9% (w/w) catalyst loading, 328 K reaction temperature, 18:1 methanol to P-UCO feed mole ratio, and 350 rpm stirring speed). Furthermore, the reusability study of the Diaion PA306s catalyst gave a similar triglyceride conversion after a couple of cycles without losing its catalytic activity. A dry purification technique was found to give the lowest percentage of glycerides and glycerine content and, therefore, was chosen as the best biodiesel purification route.